Faipar a dualizmus kori Dráva mente térségében - Szabó, Máté (Közép-Európai Közlemények, 2023)
In the rapidly industrializing Hungary, the wood industry became an important economic branch in the country by the beginning of the 20th century, which also played a significant role in the country's foreign trade. This industry was extremely important in the area I studied, as the forest cover along the Dráva was above the national average, and the quality of the forest stock also had an international reputation. In the last third of the 19th century, domestic and foreign demand for wood products increased, which was accompanied by an increase in the purchase prices of wood raw materials. During this period, the logistical and transportation possibilities of the region improved, as the railway lines – built almost completely until the war – networked the region. In addition to transport on the river, crossing opportunities also increased, so the raw material could reach a processing unit more and more quickly. In the age of dualism, a strong stratum of forest owners and entrepreneurs in the wood industry developed. In my study I present the larger wood companies in the region, the results of the plants, the operation and extent of the industry, and their market relations. Major wood industry enterprises were established mainly in the larger estates (Bellye, Dárda, Barcs, Berzence) or through citizenship in the territory of certain large municipalities. Outstanding among these was the Beliscian plant beyond the Dráva, which in two decades had become the largest timber company in Central Europe, employing thousands of people.